2022
DOI: 10.1371/journal.pone.0275951
|View full text |Cite
|
Sign up to set email alerts
|

Exploring spatial variations in level and predictors of unskilled birth attendant delivery in Bangladesh using spatial analysis techniques: Findings from nationally representative survey data

Abstract: Background Bangladesh has failed to meet the United Nations goal for reducing maternal mortality in the last decade. The high prevalence of unskilled birth attendant (UBA) delivery (47%) has resulted in negative consequences for the health of mothers and newborn babies in the country. Spatial variations in UBA delivery and its predictors are yet to be explored in Bangladesh, which could be very helpful in formulating cost-effective policies for reducing that. This study examines the spatial variations in UBA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
(50 reference statements)
0
1
1
Order By: Relevance
“…Based on the 2016 EDHS data, the prevalence of unskilled birth attendants (UBA) in Ethiopia was 66.93% with 95% CI (66.39, 69.12). This study nding was higher than studies conducted in Chad 61.5% [14], in Bangladesh 47.1% [23] and in Sub-Sharan African 44% [13]. The possible reason for this spatial variation might be due to women's cultural attitudes and social beliefs differences across the countries.…”
Section: Discussioncontrasting
confidence: 61%
“…Based on the 2016 EDHS data, the prevalence of unskilled birth attendants (UBA) in Ethiopia was 66.93% with 95% CI (66.39, 69.12). This study nding was higher than studies conducted in Chad 61.5% [14], in Bangladesh 47.1% [23] and in Sub-Sharan African 44% [13]. The possible reason for this spatial variation might be due to women's cultural attitudes and social beliefs differences across the countries.…”
Section: Discussioncontrasting
confidence: 61%
“…The reference forecast and Scenario 3 are scenarios that consider regional differences by administrative division. This is because several reports on Bangladesh have found that community and regional characteristics are associated with decisions regarding the place of birth and birth attendants [24,25]. Bangladesh has eight administrative divisions, and the education level of women, wealth of households, and utilisation of maternal and child health services, such as ANC visits and facility delivery rates, vary by division.…”
Section: Resultsmentioning
confidence: 99%